2020
DOI: 10.1016/j.foodres.2020.109589
|View full text |Cite
|
Sign up to set email alerts
|

Phlorotannins: From isolation and structural characterization, to the evaluation of their antidiabetic and anticancer potential

Abstract: Glossary of Abbreviations iNOS: inducible nitric oxide synthase COX-2: cyclooxygenase 2 CAT: catalase SOD: superoxide dismutase GSH-px: glutathione peroxidase Bcl-2: -cell lymphoma 2 (anti-apoptotic protein of the Bcl-2 family) GLUT-4: glucose transporter type Fas: cell surface death receptor XIAP: X-linked inhibitor of apoptosis protein FLIP: FLICE (caspase 8)-inhibitory protein AKT: serine/threonine-specific protein kinase, also known as PKB (protein kinase B) Bid: BH3 interacting domain death agonist (pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 142 publications
(179 reference statements)
0
45
0
Order By: Relevance
“…However, the level of complexity for the major phlorotannin component (m/z [M − 2H] 2− = 1117; apparent MW 2234; possible fucaphlorethol of DP 18) highlighted in this paper illustrates the daunting extent of data interpretation required to make inferences of overall structure. Also, MS-based analyses are inherently limited by their mass range and cannot deal with the high molecular weight phlorotannin species known to be present in brown seaweeds [2,15]. However, the molecular range could be extended by using other MS systems with higher MW ranges such as MALDI-TOF, as described previously e.g., [32].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the level of complexity for the major phlorotannin component (m/z [M − 2H] 2− = 1117; apparent MW 2234; possible fucaphlorethol of DP 18) highlighted in this paper illustrates the daunting extent of data interpretation required to make inferences of overall structure. Also, MS-based analyses are inherently limited by their mass range and cannot deal with the high molecular weight phlorotannin species known to be present in brown seaweeds [2,15]. However, the molecular range could be extended by using other MS systems with higher MW ranges such as MALDI-TOF, as described previously e.g., [32].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the MS 2 evidence ( Table 2) strongly suggested that the phlorotannin oligomers were fucophlorethols as they contained aryl ether linkages [2]. Due to the three-way symmetry of the phloroglucinol molecule, -C-C-phenyl linkages are always effectively meta-orientated [15]. However, PG units attached through aryl ether bridges can occur at hydroxyls at ortho, meta or para positions on the rings so the possibilities for different isomeric structures are large especially as the DP increases.…”
Section: Structural Information From Ms 3 Fragmentation Datamentioning
confidence: 98%
See 3 more Smart Citations